ADMINISTRATION OF MUCOLYTICS WITH DIRECT ACTION IN PEDIATRIC PRACTICE - O. I. Simonova ("Paediatrician" Publishers LLC, 2011)
Authors consider direct mucolytic action of N-acetylcysteine and all its drug forms (ACC) with antioxidant and antitoxic effects. The drug is effective for treatment of different inflammatory diseases of respiratory tract in children with increase of bronchial secretion vi scosity including infected one. The article describes indications, contraindications and peculiarities of treatment with acetylcysteine in children.